Design of Miniature Zebra Crossing Violator Detection at Traffic Lights Based on Internet Of Things - Alwi, Lukman; Zarory, Hilman; Faizal, Ahmad; Mursyitah, Dian (PROtek : Jurnal Ilmiah Teknik Elektro, 2025)
A frequen problem in riau province is the problem of traffic lights at zebra crossing, where  drivers often cross the stop line. Many drivers, especially at traffic lights, cross the stop line, potentially causing congestion and accidents. To overcome these problem, technology is needed that can detect and monitor the number of zebra crossing violation remotely. One of the technological solutions is the use of iot-based esp32 cam camera modue and pir sensor, sepaker. This research aim to create a device that can detect drivers eho exceed the stop line at the zebra crossing violation detecion system at iot-based traffic lights. Five violations were tested using a stopwatch to measure the  desice’s response time. Sensor 1 nad 2 detected the fastest violation at 0.34 seconds and 0.55 second respectively. Buzzer has a response time of 0.34 seconds, esp32 cam has a response time of 0.55 seconds, and telegram has response time occurs at a distance of 19 cm. The results showed that the pir sensor can detect the vehicles that cross the stop line, and the esp32 cam can capture image of the telegram as evidence of the violation within a distance of 20 cm, outside  this range the sensor connot detect the violation